Two promising candidates for paratransgenesis, Elizabethkingia and Asaia, increase in both sexes of Anopheles gambiae mosquitoes after feeding - Richardson K. Egyirifa; Jewelna Akorli (Malaria Journal, 2024)
Abstract Background The male mosquito microbiome may be important for identifying ideal candidates for disease control. Among other criteria, mosquito-associated symbionts that have high localization in both male and female mosquitoes and are transmissible through both vertical and sexual routes are desirable. However, mosquito microbiome studies have mainly been female-focused. In this study, the microbiota of male and female Anopheles gambiae sensu lato (s.l.) were compared to identify shared or unique bacteria. Methods Late larval instars of Anopheles mosquitoes were collected from the field and raised to adults. Equal numbers of males and females of 1-day-old non-sugar-fed, 4–5-day-old sugar-fed and post-blood-fed females were randomly selected for whole-body analyses of bacteria 16S rRNA. Results Results revealed that male and female mosquitoes generally share similar microbiota except when females were blood-fed. Compared to newly emerged unfed mosquitoes, feeding on sugar and/or blood increased variability in microbial composition (⍺-diversity), with a higher disparity among females (39% P = 0.01) than in males (29% P = 0.03). Elizabethkingia meningoseptica and Asaia siamensis were common discriminants between feeding statuses in both males and females. While E. meningoseptica was particularly associated with sugar-fed mosquitoes of both sexes and sustained after blood feeding in females, A. siamensis was also increased in sugar-fed mosquitoes but decreased significantly in blood-fed females (LDA score > 4.0, P < 0.05). Among males, A. siamensis did not differ significantly after sugar meals. Conclusions Results indicate the opportunities for stable infection in mosquitoes should these species be used in bacteria-mediated disease control. Further studies are recommended to investigate possible host-specific tissue tropism of bacteria species which will inform selection of the most appropriate microbes for effective transmission-blocking strategies.